Drying Kinetics of Button Mushroom in Fluidized Bed - Singh, Sudhir Kumar; Narain, Maharaj; Kumbhar, B K (Journal of Agricultural Engineering, 2007)
Kinetics of sliced edible mushrooms were studied during fluidized bed drying at different temperatures (50,60, 70, 80 & 90degree C). Prior to drying, sliced samples were pretreated: a) blanching, b) soaking in 0.5% KMS (Potassium Metabisulphite) solution, c) soaking in 1% KMS, 0.2% Citric Acid, 6% Sugar & 3% Salt, d) blanching and soaking in 0.5% KMS and e) blanching and soaking in 1% KMS, 0.2 % Citric Acid, 6% Sugar and 3% Salt. It was found that drying rate was proportional to temperature. It was also found that drying behaviour followed the Arrehenius relationship. The values of energy of activation ranged between 12.128 to 40.149 kJ/mol. Exponential model was found to be better fit than Page's model for predicting the drying behaviour of button mushroom.